Do audit firm rotation, auditor retention, and joint audits matter? – An experimental investigation of bank directors' and institutional investors' perceptions. Issue 1 (25th February 2018) - Quick, Reiner; Schmidt, Florian
Abstract : As a consequence of the global financial and economic crisis, the European Commission recently reformed the audit market. One objective was to restore public trust in the auditing profession and thus to enhance the audit function. This study investigates whether perceptions of auditor independence and audit quality are influenced by audit firm rotation, auditor retention and joint audits, because regulators argue that these instruments can improve auditor independence and audit quality. Therefore, we conduct an experiment with bank directors and institutional investors in Germany. The results indicate a negative main effect for joint audits on perceived auditor independence, and that a rotation cycle of 24 years marginally significantly impairs participant perceptions of audit quality, compared to a rotation cycle of only ten years. Besides the main effects, planned contrast tests suggest a negative interaction between rotation and joint audit on participant perceptions of auditor independence. Moreover, a negative interaction effect is revealed between rotation after 24 years and retention on perceptions of audit quality. It is particularly noteworthy that we failed to identify a positive impact of the regulatory measures taken or supported by the European Commission on perceptions of auditor independence and audit quality.